2011
DOI: 10.2522/ptj.20100262
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity of the Extended ICF Core Set for Stroke: An International Delphi Survey of Physical Therapists

Abstract: According to the physical therapists, the current version of the Extended ICF Core Set for stroke largely covers the types of problems that their interventions address. However, some aspects of functioning emerged that are not yet covered and may need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Consequently, these results support its use in community stroke rehabilitation services in New Zealand. The three categories in this study that were not covered by the EICSS but are found in the ICF, have also been found relevant in other studies; s760 structure of the trunk, d660 assisting others and e535 communication services, systems and policies which supports the recommendations of previous researchers for these categories to be included in the EICSS [8,16,17].…”
Section: Insert Table 7 Here Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Consequently, these results support its use in community stroke rehabilitation services in New Zealand. The three categories in this study that were not covered by the EICSS but are found in the ICF, have also been found relevant in other studies; s760 structure of the trunk, d660 assisting others and e535 communication services, systems and policies which supports the recommendations of previous researchers for these categories to be included in the EICSS [8,16,17].…”
Section: Insert Table 7 Here Discussionsupporting
confidence: 65%
“…Physicians, physiotherapists, and occupational therapists all reported that ICF category b765 involuntary movement, should be included and noted the absence of categories related to neglect, posture and patient education in both the ICF and EICSS [16][17][18]. In addition, both physiotherapy and occupational therapy professionals thought the following six ICF categories needed to be included in the EICSS: b720 mobility of bone functions, s760 structure of the trunk, s770 additional musculoskeletal structures, d435 moving objects with the lower extremity, d650 caring for household objects and e140 products and technology for culture recreation and sport [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of Core Set categories for stroke patients has been cited in the literature not limiting its clinical applicability. 26,30,31,32 Regarding the Brief Core Set, only half of the categories could be related to the FIM. The categories that were not were not included were: b110 consciousness functions, b114 orientation functions, b730 muscle power functions, s110 structure of brain and e310 immediate family.…”
Section: Discussionmentioning
confidence: 99%
“…Resampling methods are a good alternative [43]. Among them, the non-parametric bootstrap [44,45] should be highlighted, not only due to its widespread use but also because it is used to analyze the results of Delphi experiments, although as mentioned before, only in medical studies [46][47][48]. However, it was only a matter of time before the bootstrap would be used in other areas, like technology and innovation, as we do in this paper.…”
Section: Non-parametric Bootstrap Analysismentioning
confidence: 97%